Language Problem in Bangladeshi Children with Autism spectrum disorder : Observation through a Neurolinguistics Approach (Northern International Medical College Journal, 2018)
Background : Autism spectrum disorder (ASD) covers a set of developmental disabilities that can cause significant social, communication, and behavioral challenges.Objective : It was aimed to find out the language problem in Bangladeshi children with Autism spectrum disorder following the neurolinguistics approach.Methodology : A descriptive observational study conducted during the period of April 2014 to December 2014 in the department of Linguistics, University of Dhaka, Bangladesh among the Bangladeshi children aged between 3–12 years. A total of 10 children with normal hearing ability who were diagnosed as ASD according to the diagnostic criteria (DSM- 5 or ICD 10) were enrolled in the study purposively from two tertiary care hospitals of Dhaka city.Results : In this study total 10 children were included and their age range was 3 to 12 years. Male was predominant (90%).Consanguinity of parents was not present in most (90%) cases,60% had positive family history of mental illness, 70% had history of delivery by lower uterine section, 80% of them were term baby. 100% children had delayed speech development, 90% was unable to indicate with index finger, 90% was unable to use noun and pronoun, 90% had repetitive words, 100% had inability to take part in rhymes, 90% was unable to play with symbols, 70% had no eye to eye contact, and 90% had no reciprocal social smile.Conclusion : Language problem in the children with ASD is an under attended problem in Bangladesh. To the authors’ best knowledge this is the first neurolinguistics approach to ASD children in Bangladesh. Further large scale extensive studies would be necessary for better visualization of the extent of the issue.Northern International Medical College Journal Vol.9(2) Jan 2018: 295-299